CIVIL LIABILITY REGULATIONS FOR PRIVACY IN CYBERSPACE IN LINE WITH INFORMATION SECURITY - Homayoun Alihosseini, Hamidreza Alikarami, Rasool Ahmadifar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Privacy is one of the basic concepts related to human rights, individual freedom, and human dignity; it has been taken into consideration in different legal and moral systems including Islamic and Iranian law. Privacy is an adaptive term in terms of terminology although, in terms of concepts and examples, it contains wide angles and rules in Islamic law. Common examples of considering privacy in Islamic law and Sharia are the prohibition of inspection, search, suspicion, eavesdropping, breach of trust, backbiting, insulting, and unauthorized entry. There are various rules regarding privacy in the Iranian Constitution, the Code of Criminal Procedure, the approvals of the Supreme Council of Cyberspace, the Islamic Penal Code, etc. Protecting privacy in cyberspace is a common and new example of privacy. Due to its technical conditions, cyberspace is of considerable capacity for misuse and violation of privacy. On one hand, common cases of the violation of privacy in the virtual environment are of considerable characteristics and, on the other hand, the emergence of the virtual environment has caused new areas of the violation of privacy. Based on the technical and legal characteristics of the virtual environment and activities, it is necessary to deal with the violation of privacy in these areas. Then, the significance, role, and execution of privacy protection in virtual environment need to be guaranteed. Subsequently, in order to effectively protect privacy in cyberspace, relevant laws have to be enacted by the legislature branch in cooperation with the executive branch to eliminate the serious gap.